Does Digital Administration Drive Pedagogical Performance? Assessing the Impact of SIMPATIKA on Classroom Management in Madrasah Education - Erniati, Erniati; Khairi, Azizatul; Sasongko, Rambat Nur (JURNAL AL-TANZIM, 2026)
This study examines the influence of Digital SIMPATIKA and Contemporary Madrasah Culture on teachers’ classroom management performance, both partially and simultaneously. A quantitative survey approach was applied involving 33 teachers as research participants. Data were collected through validated and reliable questionnaires and analyzed using multiple linear regression, including partial t-tests, a simultaneous F-test, and the coefficient of determination (R²). The results show that Digital SIMPATIKA (X1) has a significant positive effect on classroom management performance (t = 2.652, p = 0.013). In contrast, Contemporary Madrasah Culture (X2) does not demonstrate a statistically significant partial influence (t = 1.587, p = 0.123). However, the regression model as a whole is statistically significant (F = 40.568, p < 0.001). The coefficient of determination (R²) is 0.730 (Adjusted R² = 0.712), indicating that approximately 71.2% of the variance in teachers’ classroom management performance can be explained by the two predictors in the model. These findings suggest that the utilization of Digital SIMPATIKA plays a stronger role in explaining classroom management performance than cultural factors within the context of this study.